Users’ Interactions with the Excite Web Search Engine: A Query Reformulation and Relevance Feedback Analysis - Spink, Amanda; Chang, Carol; Goz, Agnes; Jansen, Bernard J. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
We conducted a transaction log analysis of 51, 473 queries and 18,113 user sessions on Excite–a major Web search engine. The purpose of the study was to examine the use of query reformulation and relevance feedback by Excite users. There has been little research examining how reformulation and relevance feedback is used during Web searching. A total of 985 user search sessions. . .